2014
DOI: 10.1021/ie500606v
|View full text |Cite
|
Sign up to set email alerts
|

Process and Cost Analysis of a Biomass Power Plant with in Situ Calcium Looping CO2 Capture Process

Abstract: A novel concept is presented to capture CO2 from a large-scale (>100 MWe) dedicated biomass-fired power plant by using CaO as the CO2 sorbent. Biomass is burnt in a circulating fluidized bed at sufficiently low temperature to allow in situ CO2 capture at atmospheric pressure. The product, CaCO3, is then calcined in an interconnected oxy-fuel combustor, or calciner, that delivers CO2 ready for subsequent purification, compression, and permanent geological storage. A detailed process analysis using Honeywell’s U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Apart from reducing CO 2 emission from human activities, carbon capture and storage (CCS) [4,5], or post combustion capture (PCC), is an alternative way to reduce the CO 2 concentration in the atmosphere and alleviate global warming [6][7][8]. As the key step of CCS, capture and separation of CO 2 has spurred much research interest in experiment and theoretical modelling [9][10][11][12]. The criteria for an ideal CO 2 sorbent are high capacity, high selectivity, fast adsorption/desorption kinetics, good mechanical properties, high hydrothermal and chemical stability, as well as low cost of synthesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from reducing CO 2 emission from human activities, carbon capture and storage (CCS) [4,5], or post combustion capture (PCC), is an alternative way to reduce the CO 2 concentration in the atmosphere and alleviate global warming [6][7][8]. As the key step of CCS, capture and separation of CO 2 has spurred much research interest in experiment and theoretical modelling [9][10][11][12]. The criteria for an ideal CO 2 sorbent are high capacity, high selectivity, fast adsorption/desorption kinetics, good mechanical properties, high hydrothermal and chemical stability, as well as low cost of synthesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve an average global warming target of 2 • C, BECCS needs to contribute 14 Gt of emission reduction during 2013 to 2050 [29]. Therefore, the emission reduction potential and economy of negative emission technologies have become the research hotspots in recent years [81,82]. Although the proportion of CO 2 emissions from cement plants (6%), refineries (5%), and iron and steel plants (5%) is small, the contribution to emission reduction is still considerable [77].…”
Section: Research Objectsmentioning
confidence: 99%
“…The fundamental advantage of the system of Figure 1 respect to stand alone oxy-fired scheme is that the O 2 consumption is about 1/3 of the equivalent oxy-fired system burning the same total flow of biomass and fuel. A recent economic and process analysis of the concept of Figure 1 (Ozcan et al, 2014) has revealed the technical and economic boundary conditions for this niche application of Calcium Looping and biomass firing in power plants to be economically viable. The close similarity of each of the main reactors in the system with commercial CFBC power plants enables an evaluation of electricity and CO 2 avoided cost (Ozcan et al, 2014) that indicates that this process achieves around 43 €/ton CO 2 avoided, only slightly lower than the cost of a stand-alone oxy-fired system burning biomass operating under comparable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent economic and process analysis of the concept of Figure 1 (Ozcan et al, 2014) has revealed the technical and economic boundary conditions for this niche application of Calcium Looping and biomass firing in power plants to be economically viable. The close similarity of each of the main reactors in the system with commercial CFBC power plants enables an evaluation of electricity and CO 2 avoided cost (Ozcan et al, 2014) that indicates that this process achieves around 43 €/ton CO 2 avoided, only slightly lower than the cost of a stand-alone oxy-fired system burning biomass operating under comparable conditions. However, a further advantage of this system is that it can be adapted to a wider range of regulatory conditions and avoided cost can even take negative values when there are economic incentives for the both the storage of CO 2 from biomass firing and green certificate for biomass use in air fired power plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation